Differential Evaluation Based Secure Ad-Hoc Protocol for Vanets - Gandotra, Tamanna; Singh, Gurpadam (Asian Journal of Engineering and Applied Technology, 2019)
VANET is a special category of MANETs which is composed of moving vehicles, acting as nodes. Vehicular Ad-hoc Networks is aimed at increasing inter-vehicular communication, so that information collected in a vehicle can be shared with other vehicle users, with the aim of improving driving experience. Many studies have indicated that appropriate attack algorithms are essential to provide secure operation of a network. It has been observed that the use of optimum or sub-optimum values are ignored while detecting the wormhole attacks in VANETs. The use of differential evolution is ignored in existing literature which can find optimum values for attack detection based VANETs. It has been observed that the proposed technique outperforms existing techniques in terms of packet collision and throughput.